2013
DOI: 10.1074/jbc.m113.529727
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Role of ZMIZ2 Protein in Regulating the Activity of the Wnt/β-Catenin Signaling Pathway

Abstract: Background: ZMIZ2 is a transcriptional coactivator, but its biological role has not been fully investigated. Results: We demonstrate a promotional role of ZMIZ2 in ␤-catenin-mediated transcription and cell growth using a variety of biologically relevant in vitro and in vivo approaches. Conclusion: ZMIZ2 is a coactivator of the Wnt/␤-catenin signaling pathway. Significance: This study explores a novel mechanism for PIAS-like proteins in regulating Wnt signaling pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 61 publications
1
19
0
1
Order By: Relevance
“…It is reported that ECT2 depletion impairs tumorigenic growth of NSCLC cell 20 . ZMIZ2 plays a role in regulating the activity of the Wnt/β-catenin signaling pathway 21 . FMNL3 is involved in regulation of cell morphology and cytoskeletal organization 22 .…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that ECT2 depletion impairs tumorigenic growth of NSCLC cell 20 . ZMIZ2 plays a role in regulating the activity of the Wnt/β-catenin signaling pathway 21 . FMNL3 is involved in regulation of cell morphology and cytoskeletal organization 22 .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it has been shown that Zimp7 has a role in regulating the activity of the Wnt/β-Catenin signaling pathway in mammalian cells. Zimp7 is shown to physically interact with β-Catenin and enhance Wnt/ β-Catenin-mediated transcription (Lee et al, 2013). Moreover, in this report Zmiz2 null mice exhibit down-regulation of Axin2, a downstream target gene of β-Catenin.…”
Section: Introductionmentioning
confidence: 83%
“…The viral supernatant was centrifuged briefly to remove cellular debris and stored at -80°C. Lentivirus infection was carried out in the presence of 6 mg/ml Polybrene [54,55].…”
Section: Methodsmentioning
confidence: 99%